2020
DOI: 10.1039/d0qi00200c
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the complexation mechanism of actinide(iii) and lanthanide(iii) with a new tetradentate phenanthroline-derived phosphonate ligand

Abstract: The separation and complexation mechanisms of actinide(iii) and lanthanide(iii) with a new phenanthroline-derived phosphonate ligand were studied experimentally and theoretically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 69 publications
10
58
0
Order By: Relevance
“…Based on the single crystal structure of the 1 : 1 Eu III complex with L 1 (Figure 6), the 10‐coordinated 1 : 1 Eu III and Am III complexes with L 1 were optimized (Figure 9). Similar complexation modes of the 1 : 1 Eu III or Am III complexes have also been reported in other tetradentate phenanthroline derivatives [9f,10a,b,26] . For the 1 : 2 species, the 10‐coordinated Am III and Eu III complexes with L 1 were also optimized (Figure 9) on the basis of other similar 1 : 2 Eu III complexes that have been confirmed by single X‐ray crystallography in [Eu(CyMe 4 ‐BTPhen) 2 NO 3 ] 2+ and [Eu(CyMe 4 ‐BTBP) 2 NO 3 ] 2+ cations [8a,27] .…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Based on the single crystal structure of the 1 : 1 Eu III complex with L 1 (Figure 6), the 10‐coordinated 1 : 1 Eu III and Am III complexes with L 1 were optimized (Figure 9). Similar complexation modes of the 1 : 1 Eu III or Am III complexes have also been reported in other tetradentate phenanthroline derivatives [9f,10a,b,26] . For the 1 : 2 species, the 10‐coordinated Am III and Eu III complexes with L 1 were also optimized (Figure 9) on the basis of other similar 1 : 2 Eu III complexes that have been confirmed by single X‐ray crystallography in [Eu(CyMe 4 ‐BTPhen) 2 NO 3 ] 2+ and [Eu(CyMe 4 ‐BTBP) 2 NO 3 ] 2+ cations [8a,27] .…”
Section: Resultssupporting
confidence: 74%
“…As listed in Table 1, the cumulative stability constants (log β ) for the formation of 1 : 1 and 1 : 2 complexes of NdL 3+ and NdL 2 3+ with L 1 were determined as 6.15±0.01 and 10.48±0.10, respectively, which are around one order of magnitude larger than that of the corresponding 1 : 1 and 1 : 2 Nd III complexes with L 2 (log β 1 =5.16±0.15, log β 2 =10.07±0.03), C2‐POPhen (5.15±0.01) [10a] and C4‐POPhen (5.43±0.02) [10b] under the same conditions. These results suggest that the tetradentate L 1 has stronger affinity to lanthanides than those of the tridentate L 2 or tetradentate phenanthroline‐derived phosphonate type ligands, further confirming the stronger binding ability of phosphine oxide (−P=O(R) 2 ) group than that of phosphonate (−P=O(OR) 2 ) moiety toward lanthanides.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…33 Recently, one class of N,O-mixed phenanthroline-derived phosphonate ligands has been developed for the extraction actinides over lanthanides. 34,35 It has been found that C2-POPhen held more extraction capability toward trivalent lanthanides and actinides than the N,N 0 -diethyl-N,N 0 -ditolyl-2,9-diamide-1,10-phenanthroline (Et-Tol-DAPhen) ligand. 36 It is notable that the replacement of phosphonate (-PQO(OR) 2 ) with phosphine oxide (-PQO(R) 2 ) could intensify the basicity of O donors.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated protonation constants of four BTPhen ligands are presented in Table 1 . As we can see from Table 1 , the original large dipole moment of phenanthroline makes it able to coordinate with H + even with the effect of withdrawing electrons by biliteral triazine [ 32 ]. The protonation process caused the alteration of the chemical environment of H3, H4, H5, H6, H7, and H8 at the corresponding carbon C3, C4, C5, C6, C7, and C8.…”
Section: Resultsmentioning
confidence: 99%